Ab Initio Materials Science and Engineering using the Molecular Dynamics Method for Total Energy Pseudopotential Calculations - Payne, M. C.; Tarnow, E.; Bristowe, P. D.; Joannopoulos, J. D. (Molecular simulation, 1989)
A description of the total energy pseudopotential technique and of Car and Parrinello's molecular dynamics method is given. A detailed investigation of the extent to which the electronic degrees of freedom in the molecular dynamics method should be regarded as classical degrees of freedom is presented. It is shown that a cancellation of the errors in the Hellmann-Feynman forces occurs when the molecular dynamics equations of motion are used to evolve the electronic degrees of freedom during a dynamical simulation of the ionic system. Applications of the molecular dynamics method to study surface reconstructions and grain boundaries in germanium and defects in arsenic tri-selenide are briefly described and the possibility of using ab-initio methods to study problems in materials science and engineering is discussed.